Ответ:
Объяснение:
По формуле
по т.Виета
(x - 1)(x + 4)
допустим: x²+3x-4=0
D = b^2 - 4ac, где a=1, b=3, c=-4, тогда:
D = 9 + 16 = 25 = 5^2
x1 = (-b + √D) \ 2a = (-3 + 5) \ 2 = 1
x2 = (-b - √D) \ 2a = (-3 - 5) \ 2 = -4
разложение: a(x - x1)(x - x2) = (x - 1)(x + 4)
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Объяснение:
По формуле![ax^{2} +bx+c=(x-x_{1} )(x-x_{2} ) ax^{2} +bx+c=(x-x_{1} )(x-x_{2} )](https://tex.z-dn.net/?f=ax%5E%7B2%7D%20%2Bbx%2Bc%3D%28x-x_%7B1%7D%20%29%28x-x_%7B2%7D%20%29)
по т.Виета
Ответ:
(x - 1)(x + 4)
Объяснение:
допустим: x²+3x-4=0
D = b^2 - 4ac, где a=1, b=3, c=-4, тогда:
D = 9 + 16 = 25 = 5^2
x1 = (-b + √D) \ 2a = (-3 + 5) \ 2 = 1
x2 = (-b - √D) \ 2a = (-3 - 5) \ 2 = -4
разложение: a(x - x1)(x - x2) = (x - 1)(x + 4)